The Impact of Internal Performance and Macroeconomic Conditions on Profitability in Indonesian Banking From 2015-2017 - I Wayan Sunarya (Jurnal Manajemen dan Kewirausahaan, 2018)
The purpose of this study is to analyze and measure the effect of internal performance and macroeconomics conditions  on profitability in Indonesian banking (conventional  and syariah bank) from 2015-2017. This research uses Granger of Causality and Vector Autoregressive (VAR)/Vector Error Correction Model (VECM) as a data analysis tool. The conclutions of this research  are: 1)  For conventional banks: the factors that have a positive influence to profitability (ROA) are BI Rate, NPL, inflation, and loan to   deposit ratio; 2) For Islamic banks: the factors that  have a positive influence to profitabilty (ROA) are exchange rate and inflation   https://doi.org/10.26905/jmdk.v6i2.2374